An Intradialytic Increase in Serum Interleukin-6 Levels is Associated with an Increased Mortality in Hemodialysis Patients. Issue 5 (May 2015) - Lichtenberg, Shelly; Korzets, Asher; Zingerman, Boris; Green, Hefziba; Erman, Arie; Gafter, Uzi; Rozen-Zvi, Benaya
Background: The inflammatory marker interleukin-6 (IL-6) increases early in the inflammatory cascade. The aim of this study was to evaluate whether an increase in serum IL-6 levels during a hemodialysis (HD) session is associated with mortality. Methods: 57 adult patients treated with HD for more than 1 month were prospectively studied over a 3-year follow-up period. Demographic and clinical data were collected and blood samples were drawn before and after a midweek HD session. Events of death and censoring were recorded. Results: During the 3-year follow-up, 50.8% of the patients died. In univariate Cox regression analysis, an increase in IL-6 levels during HD was associated with an increased mortality (HR 1.41 per pg/ml; 95% CI 1.06 to 1.88; P = .017). In multivariate Cox models, the only independent predictors of all-cause mortality were: an increase in IL-6 levels during dialysis (HR 1.46 per pg/ml; 95% CI 1.08 to 1.98; P = .014), higher baseline C-reactive protein (CRP) levels and older age. When predictors of an increase in serum IL-6 levels during HD were introduced into the model, mortality was still significantly associated with IL-6 elevation during dialysis (HR 1.47 per pg/ml, 95% CI 1.01 to 2.14; P = .045). Conclusions: A rise in serum IL-6 levels during a single HD session is associated with a higher mortality among HD patients, independent of predialysis CRP or IL-6 levels. The results may imply the presence of an intradialytic inflammatory response that affects survival in HD patients.